Outdoor Thermal Comfort Study on Urban Areas with Various Densities in Taipei - Ying-Ming Su; Janmichael Antoni (Engineering Proceedings, 2023)
With relatively high temperatures and evenly distributed precipitation throughout the year, outdoor thermal comfort is important in Taiwan. Thus, we discuss thermal comfort in different density areas with A: a low density (average buildings height/Street width ratio: 1.3, SVF: 0.28), B: a mid density (H/W: 2.75, SVF: 0.14), and C: a high density (H/W: 6.88, SVF: 0.11). Data were acquired through field meteorological measurements from the three sites on typical summer days from 15 to 17 July 2022. Around the Wanhua district of Taipei City, thermal comfort was obtained through the calculation of thermal comfort indices: physiological equivalent temperature (PET) and Universal Thermal Climate Index (UTCI). Results showed that different urban density areas had different thermal comforts; streets in A were more exposed to sunlight, causing the mean radiant temperature to be the highest; C had lower solar radiation and stronger wind with the highest comfort level; and B had higher air temperature but lower radiation than A. PET contributed to uncomfortableness in A. Thermal sensation vote results showed that B had the most “uncomfortable” votes because wind speed in B was the lowest. Medium-density urban areas had enough solar exposure on the pedestrian level, but not enough wind to dissipate the heat. PET was more sensitive to mean radiant temperature. These findings provide a guideline and technical reference for urban designers to mitigate the high temperatures of summer in urban areas and improve thermal comfort to create a healthy environment and encourage people to utilize outdoor environments.